2016
DOI: 10.1136/postgradmedj-2016-134328
|View full text |Cite
|
Sign up to set email alerts
|

Application of visually based, computerised diagnostic decision support system in dermatological medical education: a pilot study

Abstract: This study demonstrated that VCDDSS increases diagnostic accuracy by 18.75%, which means we can avoid possible misdiagnosis, provide better treatment, and avoid waste of medical resources. The user satisfaction is high. We expect wider application of this kind of decision support system in clinical practice, medical education, residency training, and patient education in the future. Further large-scale studies should be planned to confirm its application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In a pilot study by Chou, clinical diagnoses of 13 patients were made by 13 dermatology residents and 51 medical students before and after using VisualDx. Diagnostic accuracy increased from 63% to 81% ( p <0.01) as judged by a consultant dermatologist [21]. Despite these positive intermediate effects, the published literature, including the study reported here, provides no evidence of better patient outcomes.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In a pilot study by Chou, clinical diagnoses of 13 patients were made by 13 dermatology residents and 51 medical students before and after using VisualDx. Diagnostic accuracy increased from 63% to 81% ( p <0.01) as judged by a consultant dermatologist [21]. Despite these positive intermediate effects, the published literature, including the study reported here, provides no evidence of better patient outcomes.…”
Section: Discussionmentioning
confidence: 83%
“…In one study, its use improved the differential diagnosis of cellulitis by emergency room physicians [20]. In a pilot study, diagnostic accuracy of dermatology residents and medical students increased after using VisualDx, as judged by a consultant dermatologist [21].…”
Section: Introductionmentioning
confidence: 99%
“…47 A digital image library of skin eruptions increased diagnostic accuracy of dermatology residents by 19% in a randomised trial. 48 An interactive computed decision support system achieved up to 75% reduction in diagnostic errors relating to vignettes of neurological disorders. 49 A web-based system that facilitated internet crowdsourcing of multiple opinions improved diagnostic accuracy among junior physicians.…”
Section: Theories Of Diagnostic Reasoningmentioning
confidence: 99%
“…Computed decision support systems that generate differential diagnoses using inputted clinical data yield small improvements in diagnostic accuracy when clinicians revisit their diagnoses following a differential diagnosis generator consultation 47. A digital image library of skin eruptions increased diagnostic accuracy of dermatology residents by 19% in a randomised trial 48. An interactive computed decision support system achieved up to 75% reduction in diagnostic errors relating to vignettes of neurological disorders 49.…”
Section: Strategies To Prevent Diagnostic Errormentioning
confidence: 99%
“…The system did not specifically describe data modeling, nor is it a model centered on the learner's learning performance. For the most essential DDEDSS research, it was of little reference [3]. Hernes and Sobieska-Karpińska proposed the data modeling of talent quality evaluation [4].…”
Section: Literature Reviewmentioning
confidence: 99%